Infective endocarditis in a developing country: evaluation of 230 cases - Oğuzhan Acet; Deniz Akyol Seyhan; Selin Bardak Özcem; Gunel Guliyeva; Meral Kayıkçıoğlu; Tansu Yamazhan; Hüsnü Pullukçu; Bilgin Arda; Sercan Ulusoy; Hilal Sipahi; Meltem Taşbakan; Oğuz Reşat Sipahi (Journal of Global Antimicrobial Resistance)
AIM: In this study it was aimed to analyse the clinical characteristics and outcomes of IE cases in our hospital. BACKGROUND: Despite developments in antibiotics and medicine, infective endocarditis (IE) is associated with significant morbidity and mortality. METHODS: Patients that were followed up for definite IE (diagnosed according to modified Duke criteria) in ourhospital between March 2007 and September 2023 were analyzed retrospectively. Patients were evaluated in terms of demographic features,underlying diseases, risk factors, clinical and laboratory findings, therapy responses, complications, and mortality. RESULTS: There were 230 patients diagnosed with IE [79-52.6% femaie, aged 53.3±16.9 years, ranging 18-92 years] fulfilling the study inclusion criteria. Risk factors, complaints, laboratory findings and complications of patients was shown in Table 1. Blood culture was positive in 175 patients (75,5%). The most common etiologic agents were; S. viridans (26.08%), S. aureus (18.6%) and E. feacalis (10.8%). The antibiotherapy of 40 patients with native valve endocarditis comprised ampicillin/sulbactam and gentamicin (other therapy combinations were vancomycin and gentamicin [n=11], penicillin and gentamicin[n=38]). Nine of 49 patients with prosthetic valve endocarditis were treated with vancomycin, rifampicin and gentamicin while other nine were treated with daptomycin including therapy. In hospital mortality was (20%-46/230). Mortality rates between blood culture positive and negative cases were similar (Chi-square test p=1) while mortality in S. viridans was less than S. aureus or enterococci (Chi-square test p=0.0085, Table 2). CONCLUSIONS: IE is still associated with significant mortality. More interventions are needed to further decrease the complication and mortality rates.